DEVELOPMENT OF MATHEMATICAL CUBES AND BLOCKS MODULES WITH A SCIENTIFIC APPROACH FOR 5th GRADE ELEMENTARY SCHOOL - Hayuningtyas, Krisnani; Kristin, Firosalia; Anugraheni, Indri (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2019)
Education never get out of adequate facilities and infrastructure. These can support education. One of them is the using of teaching material. The limiting of it makes students have one handbook only and learn by using it, so they don’t practice enough on working other math problems. With these problems, researcher is encouraged to develop mathematical module cube and block with a scientific approach for 5th grade elementary school. Type of this research is research and development (R&D) with aim to know that development of mathematical cubes and block module with scientific approach for 5th grade is feasible or not. Data collection techniques used interview, observation, documentation, and questionnaire. Data analysis techniques used qualitative data analysis and quantitative data analysis. The results of the development of mathematical cubes and blocks modules with the scientific approach are said to be very feasible with a percentage of 84 from material expert, 81,34 from module expert, 83 from 5th grade teacher and 95,10 from 5th grade students.